Trigonometric applications in heuristic mode and their impact on the cognitive development of adolescents in Cauri - Paragua-Macuri, Carlos A. (2023)
The objective of the study was to evaluate the incidence of the application of trigonometric functions in a heuristic mode, on the cognitive development of adolescents from Cauri. In this sense, the autonomous variable was applied to the dependent variable to generate an effect of improvement in cognitive development. The study had an explanatory level, basic type and quasi-experimental design. The population was made up of 335 young people from Cauri, from which a non-random sample of 46 was selected, who were grouped as follows: 20 in the experimental group and 26 in the control group. The data were collected through three evaluative written tests, each with 10 propositions to develop. The data obtained were processed in Microsoft Excel, which allowed the calculation of the statistics corresponding to the descriptive and inferential analysis. The results showed that the test T value is equal to 6.75, located to the right of the critical t equal to 1.645, for 95% reliability and 5% significance, that is, in the rebound range. Consequently, it was proven that the implementation of trigonometric functions in a heuristic mode positively impacts the cognitive development of the young people analyzed.